2019
DOI: 10.1108/ejm-06-2017-0417
|View full text |Cite
|
Sign up to set email alerts
|

Customer in-role and extra-role behaviours in a retail setting

Abstract: Purpose Prior research does not provide a clear picture of how managers can effectively manage customer in-role and extra-role behaviours in a retail setting. This study aims to test the differential impact of the two main customer relationship predictor paths – identity-based and satisfaction-based paths – on customer in-role and extra-role behaviours. Design/methodology/approach A random sample of 500 customers from the flagship store of an up-market, international department store chain participated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 95 publications
2
49
0
2
Order By: Relevance
“…Prior research has found positive (Eisingerich et al, 2014;Groth, 2005), null (Paulssen et al, 2019) and negative (Verleye et al, 2014) relationships between satisfaction and customer feedback sharing. Such discrepant findings may be a function of two contrasting effects:…”
Section: Study 2 (Grocery) -The Moderating Role Of Service Qualitymentioning
confidence: 93%
See 4 more Smart Citations
“…Prior research has found positive (Eisingerich et al, 2014;Groth, 2005), null (Paulssen et al, 2019) and negative (Verleye et al, 2014) relationships between satisfaction and customer feedback sharing. Such discrepant findings may be a function of two contrasting effects:…”
Section: Study 2 (Grocery) -The Moderating Role Of Service Qualitymentioning
confidence: 93%
“…In studies of customer citizenship behavior, the goal of helping others is seen as a primary driver of helpful behaviors (Choi and Lotz, 2016). Indeed, customer extra-role behaviors have been defined as "voluntary acts on behalf of customers" (Paulssen et al, 2019(Paulssen et al, , p. 2504. Relatedly, concern for other consumers is a leading predictor of both direct and online WOM behavior (Hennig-Thurau et al, 2004;Sundaram et al, 1998).…”
Section: Consumer Suggestionmentioning
confidence: 99%
See 3 more Smart Citations